The story of Christian spirituality: two thousand years, from East to West - Mursell, Gordon (A lion book, 2001)
The Christian faith has had a phenomenal impact on the development of the western world. This beautifully illustrated introduction to Christian spirituality through the centuries covers all the major traditions - East and West, Catholic, Orthodox and Protestant, with special articles on key spiritual concepts, practices and movements that continue to influence the way people all over the world live their lives in response to God. It also includes information on people and movements from outside the Church that have influenced Christian life and thought throughout two thousand years. Also included are extracts from over 100 of the greatest Christian spiritual writings - from the Gospels, through the early Church Fathers, the saints and mystics, the reformers and modern spiritual writers such as Scott Peck and CS Lewis. Timelines and geographical locators help the reader place each figure in relation to other people, places and events, and glorious colour illustrations help to tell the fascinating story of how human beings throughout the centuries have interpreted and lived out their Christian faith.